Australasian Egyptology Conference 4 : papers from the fourth Australasian Egyptology Conference, Monsh University, Melbourne, 16-18 September 2016 : dedicated to Gillian E. Bowen - Bowen, Gillian E.; Hope, Colin A.; Parr, Bruce E.; Rindi Nuzzolo, Carlo (Archaeopress Egyptology, 2023)
This text presents papers from the fourth Australasian Egyptology Conference held at Monash University in 2016 and dedicated to Gillian E. Bowen, who retired from Monash that year. The contributions include several on Egypt's Western Desert where Monash has been engaged in fieldwork for many years in the the Dakhleh Oasis.